2017
DOI: 10.1126/science.aag1417
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal cholesterol activates mTORC1 via an SLC38A9–Niemann-Pick C1 signaling complex

Abstract: The mechanistic target of rapamycin complex 1 (mTORC1) protein kinase is a master growth regulator that becomes activated at the lysosome in response to nutrient cues. Here we identify cholesterol, an essential building block for cellular growth, as a nutrient input that drives mTORC1 recruitment and activation at the lysosomal surface. The lysosomal transmembrane protein, SLC38A9, is required for mTORC1 activation by cholesterol through conserved cholesterol-responsive motifs. Moreover, SLC38A9 enables mTORC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
434
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 435 publications
(468 citation statements)
references
References 36 publications
20
434
1
Order By: Relevance
“…In our previous work, we found that SLC38A9 and the cytosolic sensor CASTOR1 both contribute to arginine sensing by mTORC1 (Chantranupong et al, 2016; Wang et al, 2015), and we hypothesize that different cell types use these sensing branches to varying extents, depending on whether they obtain amino acids mostly in the free form or through the digestion of proteins. Recent work shows that SLC38A9 also has an important role in cholesterol sensing upstream of mTORC1 (Castellano et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…In our previous work, we found that SLC38A9 and the cytosolic sensor CASTOR1 both contribute to arginine sensing by mTORC1 (Chantranupong et al, 2016; Wang et al, 2015), and we hypothesize that different cell types use these sensing branches to varying extents, depending on whether they obtain amino acids mostly in the free form or through the digestion of proteins. Recent work shows that SLC38A9 also has an important role in cholesterol sensing upstream of mTORC1 (Castellano et al, 2017). …”
Section: Discussionmentioning
confidence: 99%
“…In particular, cholesterol delivered to the lysosome by endocytosed LDL particles induced the recruitment of mTORC1 to the lysosomal surface (Castellano et al, 2017). Combining in vitro and in cell experiments, it was shown that lysosomal cholesterol levels affect the activation status of the Rag GTPases.…”
Section: Feedback Regulation Of Mtorc1 Activity By Lipid-derived Signalsmentioning
confidence: 99%
“…In mammalian cells, amino acids, along with glucose and cholesterol, trigger the lysosomal translocation of mTORC1 via a mechanism that requires the Ras-related, heterodimeric Rag guanosine triphosphatases (GTPases) and the pentameric Ragulator complex Castellano et al, 2017;Efeyan et al, 2013;Sancak et al, 2008Sancak et al, , 2010. The Rag GTPases, composed of RagA or RagB (which are functionally equivalent to each other) in complex with RagC or RagD (also functionally equivalent), are thought to directly bind to the Raptor subunit of mTORC1, anchoring it to the lysosomal membrane (Kim et al, 2008;Sancak et al, 2008Sancak et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%